Effect of substrate temperature on GaAs nanowires growth directly on Si (111) substrates by molecular beam epitaxy. (2020) - Khaing Oo, Kay; Vorathamrong, Samatcha; Panyakeow, Somsak; Praserthdam, Piyasarn; Ratanathammaphan, Somchai
Abstract: We have demonstrated growth of GaAs nanowires directly on Si (111) substrates by Ga-assisted technique using molecular beam epitaxy. In this work, Ga droplet forming and nanowire growth are performed at the same substrate temperature. Effect of substrate temperature while droplet forming with nanowire growth on the GaAs nanowire structural properties is investigated by Scanning Electron Microscope (SEM) and X-ray Diffraction (XRD). Nucleation of the GaAs nanowires strongly depends on the substrate temperature. The results show that density, length, and diameter of the GaAs nanowires relate to the substrate temperature.